Coronary Stent Strut Fractures: Classification, Prevalence and Clinical Associations - Schochlow, Katharina; Weissner, Melissa; Blachutzik, Florian; Boeder, Niklas F.; Tröbs, Monique; Lorenz, Liv; Dijkstra, Jouke; Munzel, Thomas; Achenbach, Stephan; Nef, Holger; Gori, Tommaso (Journal of Clinical Medicine, 2021)
Introduction. The frequency, characteristics and clinical implications of Strut fractures (SFs) remain incompletely understood. Methods and results. A total of 185 (160 patients) newer-generation drug-eluting stents (DES) were imaged. SFs were found in 21 DES (11.4%) and were classified in four patterns: one single stacked strut (41%); two or more stacked struts (23%); deformation without gap (27%); transection (9%). In multivariable analysis, calcific and bifurcation lesions were associated with SF in DES (OR: 3.5 [1.1-11] and 4.0 [2.2-7.2], p < 0.05). Device eccentricity and asymmetry as well as optical coherence tomography (OCT) features of impaired strut healing were also associated with SF. The prevalence of fractures was similar in a set of 289 bioresorbable scaffolds (BRS). In a separate series of 20 device thromboses and 36 device restenoses, the prevalence of SF was higher (61.2% of DES and 66.7% of BRS, p < 0.001 for both), with a higher frequency of complex SF patterns (p < 0.0001). In logistic regression analysis, fractures were a correlate of device complications (p < 0.0001, OR = 24.9 [5.6-111] for DES and OR = 6.0 [1.8-20] for BRS). Discussion. The prevalence of OCT-diagnosed SF was unexpectedly high in the setting of elective controls and it increased by about three-fold in the setting of device failure. Fractures were associated with increased lesion complexity and device asymmetry/eccentricity and were more frequent in the setting of device failure such as restenosis and thrombosis.
CRIS-Team WoS Importer:2021-05-07